2014
DOI: 10.1097/jom.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Low Back Problems in a Major Self-Insured Workforce

Abstract: Approaches marked by higher resource utilization and lower guideline congruence are linked to greater low back pain total costs. Total cost is a needed input for guideline development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Twelve (48 %) studies examined data from private health plans in the US [ 22 – 33 ]. Six (24 %) studies examined data from worker’s compensation (WC) plans in the US [ 34 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve (48 %) studies examined data from private health plans in the US [ 22 – 33 ]. Six (24 %) studies examined data from worker’s compensation (WC) plans in the US [ 34 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…lost productivity) account for a majority of the total costs of spine pain they are difficult to measure and often complex. Only 5/25 (20 %) measured these costs; they were generally lower for patients receiving chiropractic care [ 33 , 35 , 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an association between chiropractic care and lower utilization of costly spine services such as all-class medications, diagnostic imaging, spinal injections, and surgery. [14][15][16] Two of these studies evaluated the cost of low back pain management when DCs were the first provider seen for an episode of care. In both studies when a DC was the portal of entry provider, the total cost was lower when compared to low back pain patients that had other entry points into the healthcare delivery (eg, physical therapy, medical specialty, etc) system.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies when a DC was the portal of entry provider, the total cost was lower when compared to low back pain patients that had other entry points into the healthcare delivery (eg, physical therapy, medical specialty, etc) system. 15 Another study in a commercially insured population showed low back pain episodes initiated with DCs cost 20% less than those initiated with physicians. 17 Our findings and these other studies provide evidence suggesting that DCs can play an important role in the cost-effective management of low back pain populations and can be an integral resource to patients, providers, and policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 When chiropractic services are integrated into medical systems, the results may include improved patient outcomes, decreased use of other health care services, greater likelihood of adherence to clinical practice guidelines, satisfaction among stakeholders, and decreased health care costs. 7,18,19 Barriers to chiropractic integration into medical settings may exist. One barrier may be the lack of interprofessional education.…”
Section: Discussionmentioning
confidence: 99%